Respuesta :

Answer:

∠M = 70°

Step-by-step explanation:

∠M = 180° - (∠L + ∠N) [Angle Sum Property]

∠M = 180° - (73° + 37°)

∠M = 180° - 110°

∠M = 70°

Hope it helps ⚜

Answer:

70° = m ∠M

Step-by-step explanation:

Given,

  • m ∠L = 73°
  • m ∠N = 37°

According to the Angle Sum Property of Triangles, we can say that the 3 angles in a triangle will always sum up to 180°. So, by using this property,



180° = m ∠L +  m ∠M + m ∠N

180° = 73° + 37° + m ∠M

180° = 110° + m ∠M
180° - 110° = m ∠M
70° = m ∠M

_________________

Hope it helps!

[tex]\mathfrak{Lucazz}[/tex]

ACCESS MORE

Otras preguntas